P7.11 HIGH ANKLE-BRACHIAL INDEX IS ASSOCIATED WITH INCREASED AORTIC PULSE WAVE VELOCITY: THE CZECH POST-MONICA STUDY - P. Wohlfahrt; M. Ingrischová; D. Palouš; A. Krajcoviechová; J. Seidlerová; M. Dolejšová; M. Galovcová; J. Bruthans; V. Adámková; M. Jozífová; J. Filipovský; R. Cífková (Artery Research, 2009)
Ankle brachial index (ABI) has increasingly been used in general practice to identify patients with low ABI at high cardiovascular risk. However there is no consensus on the clinical significance of high ABI. The aim of our study was to compare large artery stiffness as a marker of cardiovascular risk in patients with low (<1.0), normal (1.0–1.4) and high ABI (>1.4). Methods: 911 patients from the Czech post-MONICA study (a randomly selected 1% representative population sample, mean age 54±13.5 years, 47% of men) were examined. ABI was measured using a handheld Doppler and aortic pulse wave velocity (aPWV) using the Sphygmocor device. Results: Of 911 patients, 28 (3.1%) had low ABI and 23 (2.5%) high ABI. There was a U-shaped association between aPWV and ABI. aPWV was significantly higher in patients with low and high ABI compared with normal ABI group (11.1±2.8, 8.3±2.3, p<0.001; 10.8±2.5, 8.3±2.3, p<0.001) and it did not differ between patients with high and low ABI (11.1±2.8, 10.8±2.5, p=0.86). In the stepwise multiple regression analysis low and high ABI were independent predictors of increased aPWV together with age, central systolic blood pressure, heart rate, BMI and hypertension. Conclusion: This is the first study showing increased aortic PWV in patients with high ABI pointing to increased cardiovascular risk in this group.